'Let me take care of you': what can healthcare learn from a high-end restaurant to improve the patient experience?. (3rd July 2021) - Korkiakangas, Terhi; Weldon, Sharon Marie; Kneebone, Roger
ABSTRACT: Background: The patient experience is associated with patient satisfaction and health outcomes, presenting a key challenge in healthcare. The objective of the study was to explore the principles of care in and beyond healthcare, namely in a three Michelin-starred restaurant, and consider what, if any, principles of care from the diners' experience could be transferrable to healthcare. Method: The principles of care were first explored as part of observational fieldwork in a healthcare day surgery unit and the restaurant respectively, focusing on communication between the professionals and the patients or the diners. Care was subsequently explored in a series of public engagement events across the UK. The events used immersive simulation to recreate the healthcare and the dining experiences for the general public, and to stimulate discussion. Results: A thematic analysis of the engagement discussions identified overarching themes in how care was experienced in and through communication; 'informed, not bombarded', 'conversation, not interrogation', 'environment is communication', and 'being met as a person'. The themes suggested how the participants in simulation felt about the care they received in real time and provided recommendations for improved clinical practice. Conclusions: While practice improvements in healthcare are challenging, the patient experience could be enhanced by learning relational aspects of care from other sectors, including the high-end restaurant industry that focuses on meeting persons' needs. Simulation provides a new kind of opportunity to bring professionals and patients together for focused discussions, prompted by immersive experiences of care and communication.